2020
DOI: 10.1177/1745691620921525
|View full text |Cite
|
Sign up to set email alerts
|

How Can Intranasal Oxytocin Research Be Trusted? A Systematic Review of the Interactive Effects of Intranasal Oxytocin on Psychosocial Outcomes

Abstract: Over the past two decades, research about the role of oxytocin (OT) in human behavior has grown exponentially. However, a unified theory of OT effects has yet to be developed. Relatedly, growing concerns about the robustness of conclusions drawn in the field have been raised. The current article contributes to this debate by reporting on and discussing key conclusions from a systematic review of published studies addressing the interactive effects of intranasal OT (IN-OT) administration on psychosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…In questioning the universality of these mechanisms across mammalian groups, our findings in this domain can also be considered within the broader context of psychological oxytocin research, which is similarly marked by interpretive challenges and heterogeneous findings (e.g. 74 ). We suggest that expanding the toolkits available to researchers, including broadening the animal models studied, will likely continue to reveal unexpected findings that require modification to existing theory (a point echoed by behavioral ecologists; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In questioning the universality of these mechanisms across mammalian groups, our findings in this domain can also be considered within the broader context of psychological oxytocin research, which is similarly marked by interpretive challenges and heterogeneous findings (e.g. 74 ). We suggest that expanding the toolkits available to researchers, including broadening the animal models studied, will likely continue to reveal unexpected findings that require modification to existing theory (a point echoed by behavioral ecologists; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The task timing of the trust game is supported by Spengler et al (2017), who reported that the oxytocin-induced inhibition of amygdala responses to fear was most effective in a time window between 45 and 70 min after administration of an oxytocin dose of 24 IU. As reviewed by Mierop et al (2020), however, adequate FIGURE 8 | Box plots of administration-induced increases in oxytocin concentration, stratified according to autism quotient (AQ) score. For each plot, the middle horizontal line denotes the median value; the box extends from the 25th to the 75th percentile values; the vertical lines extending from the box denote adjacent values (i.e., the most extreme values within 1.5 interquartile of the 25th and 75th percentile of each group); and the dots denote oxytocin concentration per investor.…”
Section: Discussionmentioning
confidence: 99%
“…The task timing of the trust game is supported by Spengler et al (2017) , who reported that the oxytocin-induced inhibition of amygdala responses to fear was most effective in a time window between 45 and 70 min after administration of an oxytocin dose of 24 IU. As reviewed by Mierop et al (2020) , however, adequate time windows following intranasal oxytocin administration are unclear. Further research is needed to advance our understanding of the task timing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there are serious methodological concerns about the validity of several observations linking oxytocin with trust, which is one of the most studied associations in social neuroscience [59][60][61][62]. For instance, the association between exogenous intranasal oxytocin and higher levels of trust [54,63] and the correlation between trust and oxytocin plasma levels [64] has been poorly replicated [60,65]. Lack of robust results linking trust with OXTR has also been evidenced in candidate gene studies.…”
Section: Plos Onementioning
confidence: 99%